Research progress of periostin and osteoporosis - Yuan, Chuyue; Li, Junyan (Frontiers in Endocrinology, 2024)
Periostin, as a unique extracellular matrix, is mainly produced during ontogeny and in adult connective tissues that bear mechanical loads, such as heart valves, skin, periodontal ligaments, tendons, and bones. By binding to the integrin on the cell surface and activating Wnt/β-catenin, NF-κB, Fak and other signaling pathways, it regulates the tissues in vivo positively or negatively, and also has different effects on the occurrence and development of various diseases. Periostin is an important factor, which can promote cell proliferation, stimulate tissue repair and maintain the integrity of the structure and function of connective tissue. It also promotes the formation, regeneration and repairation of bone. Recent studies have shown that periostin is important in bone metabolic diseases. The increased expression of periostin can affect bone mineral density at different sites, and its relationship with traditional biochemical markers of bone turnover has not been conclusively established. This article reviews the research results and potential applications of periostin in osteoporosis.